Day 4 Thu, May 09, 2019 2019
DOI: 10.4043/29220-ms
|View full text |Cite
|
Sign up to set email alerts
|

Forward Scouting: Use of Sediment Profile Imagery in Conjunction with Multibeam Echosounder Mapping for Offshore Wind Cable Routes and Site Characterization

Abstract: Selection of cable routes and wind turbine site assessments for offshore energy projects in the often-complex geology of the North American Atlantic coast entails very high risks for developers as well as state agencies: limited desktop data, patchy distribution of critical or sensitive habitats, and use conflicts, are a sampling of the risks encountered. The costs required to conduct multi-disciplined geophysical spreads including weather delays during marine mammal transit windows does not support exploring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It is particularly important to understand the effects of offshore wind development on the seafloor, which contributes significantly to ecosystem services globally (Costanza et al 1997;Liquete et al 2013;Dannheim et al 2019). Accurate seafloor habitat maps are essential for developers to appropriately site and design wind farms (Barrie et al 2014), to satisfy environmental assessment requirements, and for scientists to have a baseline from which to monitor and measure change (Shields et al 2009; Barrie et al 2014;e.g., LaFrance et al 2014;Pearce et al 2014;Schlappy et al 2014;Carey et al 2019). A review of European studies primarily conducted in soft seafloor settings concluded that knowledge on changes to benthic ecological functioning due to offshore marine renewable operations is limited and will require hypothesis-driven research combined with ecological modeling (Dannheim et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is particularly important to understand the effects of offshore wind development on the seafloor, which contributes significantly to ecosystem services globally (Costanza et al 1997;Liquete et al 2013;Dannheim et al 2019). Accurate seafloor habitat maps are essential for developers to appropriately site and design wind farms (Barrie et al 2014), to satisfy environmental assessment requirements, and for scientists to have a baseline from which to monitor and measure change (Shields et al 2009; Barrie et al 2014;e.g., LaFrance et al 2014;Pearce et al 2014;Schlappy et al 2014;Carey et al 2019). A review of European studies primarily conducted in soft seafloor settings concluded that knowledge on changes to benthic ecological functioning due to offshore marine renewable operations is limited and will require hypothesis-driven research combined with ecological modeling (Dannheim et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, benthic sampling devices (grab samples) and paradigms for consistently understanding recovery (successional stage theory, Pearson and Rosenberg 1978;Rhoads and Boyer 1982;Rhoads and Germano 1982) traditionally used in soft sediment environments are of little use in hard bottom areas (Taylor and Wilson 2003;Sheehan et al 2010). Use of high-resolution multibeam echosounder (MBES) data and high-resolution ground-truth imagery has been recommended for mapping these habitats (Kenny et al 2003;Diaz et al 2004; NOAA Habitat 2020) and has been used to characterize hard bottom and mixed habitats before construction at offshore renewable energy sites in the UK (Sheehan et al 2010;Pearce et al 2014), Norway (Schlappy et al 2014;Saskov et al 2015), and the U.S. (Carey et al 2019).…”
Section: Introductionmentioning
confidence: 99%